A Clinical Decision Support System for Remote Monitoring of Cardiovascular Disease Patients: A Clinical Study Protocol - Ventura, Filipa; Sousa, Pedro; Dixe, Maria Anjos; Ferreira, Paulo; Martinho, Ricardo; Dias, Sara Simões; Morais, João; Gonçalves, Lino M. (Frontiers in Public Health, 2022)
Introduction: Cardiovascular diseases (CVD) are the leading cause of death globally, taking an estimated 17.9 million lives each year. Cardiac rehabilitation is shown to reduce mortality and hospital readmissions, while improving physical fitness and quality of life. Despite the recommendations and proven benefits, acceptance and adherence remain low. Mobile health (mHealth) solutions may contribute to more personalised and tailored patient recommendations according to their specific needs. This study protocol aims to assess the effectiveness of a user-friendly, comprehensive Clinical Decision Support System (CDSS) for remote patient monitoring of CVD patients, primarily on the reduction of recurrent cardiovascular events. Methods and Analysis: The study will follow a multicenter randomised controlled design involving two cardiology units in the Centre Region of Portugal. Prospective CVD patients will be approached by the healthcare staff at each unit and checked for eligibility according to the predefined inclusion/exclusion criteria. The CDSS will suggest a monitoring plan for the patient, will advise the mHealth tools (apps and wearables) adapted to patient needs, and will collect data. The clinical study will start in January 2023. Discussion: The success of the mHeart.4U intervention will be a step towards the use of technological interfaces as an integrating part of CR programs. Ethics and Dissemination: The study will undergo ethical revision by the Ethics Board of the two hospital units where the study will unfold. The study was registered in ClinicalTrials.gov on 18th January 2022 with the number NCT05196802. The study findings will be published in international peer-reviewed scientific journals and encounters and in a user-friendly manner to the society.